Les fonctions discursives du Lexique Scientifique Transdisciplinaire pour aider à la compréhension et à la production d’écrits académiques - Li, Jingrao; Cavalla, Cristelle (Studia Romanica Posnaniensia, 2025)
The Transdisciplinary Scientific Lexicon (TSL) is a lexicon that transcends scientific disciplines (e.g., hypothesis, advance an argument, the objective of this study is to determine...). Mastering these elements is crucial because they fulfill essential discursive functions (DF) in the scientific genre, serving reasoning, structuring, and argumentation purposes. In this article, we propose using DFs as a bridge that links understanding and production of the TSL. To achieve this, a scientific writing training program was offered to learners, utilizing a corpus-based teaching approach and a lexical tool for scientific writing developed by our team. We will highlight the benefits of mastering DFs in terms of helping learners to understand and produce scientific texts, as well as the challenges learners face in using DFs to formulate ideas in writing.